A new species of Sasajiscymnus Vandenberg (Coleoptera: Coccinellidae) from Pakistan - Iqbal, Zafar; Nasir, Muhammad Farooq; Bodlah, Imran (Zootaxa, 2020)
A new species of a ladybird beetle, Sasajiscymnus nigritus sp. nov., is described and illustrated from Pakistan. An identification key to Pakistani species of Sasajiscymnus Vandenberg is provided. A preliminary checklist of species of Sasajiscymnus in Asia is also included.